Pengaruh Penerapan Model Pembelajaran Collaborative Learning Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti Peserta Didik Kelas IX UPT SMP Negeri 026 Pearung Kabupaten Humbang Hasundutan Tahun Pembelajaran 2024/2025 - Rani Bella Siregar; Lustani Samosir; Oloria Malau; Hanna Dewi Aritonang; Wilson Simanjuntak (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This study aims to determine the effect of the collaborative learning model on student learning outcomes. The research method used is quantitative with a pre-experimental design research type in the form of one-group pretest-posttest. The population of all 9th grade students is 62 people and a sample of 31 people through purposive sampling. The instrument in the form of a test question consists of 20 items. The results of the data analysis show that there is a positive and significant effect of the Collaborative Learning PAK and Budi Pekerti learning model on the Learning Outcomes of Class IX students, as evidenced by the tcount> ttable value, namely 14.226> 2.042. It is concluded that H0 is rejected and Ha is accepted.